Maze tests for assessing the reading comprehension of third year high school students - Monje, Marta Nalapo- 1932- (1980)
This research paper presented a set of maze tests designed to assess the reading levels and monitor the comprehension skills of third year high school students. The subjects of the study were forty five randomly selected students from the star, middle and lowest sections of the Junior class of the Rosales National High School. The Gates Reading Survey Test was administered to the subjects. Given evidence of the maze tests' reliability and validity as an assessment level for reading comprehension, they can be used to supplement other diagnostic instruments in measuring the reading performance of third year high school students.